A powerful and simple frequency formula to nonlinear fractal oscillators - Kang-Le Wang; Chun-Fu Wei (Journal of Low Frequency Noise, Vibration and Active Control, 2021)
In this work, a fractal nonlinear oscillator is successfully established by fractal derivative in a fractal space, and its variational principle is obtained by semi-inverse transform method. The variational principle can provide conservation laws in an energy form. The approximate frequency of the fractal oscillator is found by a simple fractal frequency formula. An example shows the fractal frequency formula is a powerful and simple tool to fractal oscillators.